VARIETIES OF ENGLISH CONSONANTS PRONUNCIATION AMONG ENGLISH UN-DERGRADUATE STUDENTS - Setiawan, Beni Rizki (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2016)
This research involved Thailand and Indonesia which is a multilingual country and has 749 dialects thoroughly. Dialect influences the way people speak foreign language in term of pronunciation, grammar and accent; the speech of people from different social and region. This paper investigates problems with English pronunciation among Javanese, Sundanese, Thai, and Thai-Malay students. Identifying key reasons of the pronunciation problems began by discussing the value of intelligible pronunciation and reviewing the rele-vant literature. Next, it focuses on the participants’ pronunciation problems in term of consonant phonemes. The method of this research is mixed method research. It means, the researcher employed qualitative and quantitative method to collect, to analyze, and to draw the conclusion of the data analysis. As the result, the researcher found varieties of English consonants pronunciation uttered by four dialects. Thai has difficulties in pronouncing allophones /z/, /θ/, /ð/, /ʃ/, /v/, /tʃ/, /b/, /dʒ/, /d/, /l/, /t/, /s/, /k/, /b/. Thai-Malay had difficulties in pronouncing allophones /z/, /θ/, /ð/, /ʃ/, /v/, /tʃ/, /b/, /dʒ/, /k/, /s/. Meanwhile, Javanese had difficulties in pronouncing /θ/, /ð/, /ʃ/, /v/, /tʃ/, /z/, /dʒ/, /k/, /w/, /g/. Sundanese had difficulties in pronouncing allophones /ð/, /v/, /tʃ/, /θ/, /p/, /ʃ/, /f/, /s/. Furthermore, Thai student had the highest varieties of pronouncing English consonants. Otherwise, Sundanese was the lowest one. Keywords: English consonants, Indonesian native, Thai native, pronunciation varieties.